Covering all the Bases: Preclinical Development of an Effective Staphylococcus aureus Vaccine - Scully, Ingrid L.; Liberator, Paul A.; Jansen, Kathrin U.; Anderson, Annaliesa S. (Frontiers in Immunology, 2014)
A key aspect of the pathogenesis of the Gram positive bacterium Staphylococcus aureus is its ability to rapidly adapt to the host environment during the course of an infection. To successfully establish infection, the organism deploys a variety of survival and immune evasion strategies, ranging from the acquisition of essential nutrients and expression of adhesins, which promote colonization and survival, to the elaboration of virulence factors such as capsule, which aids host immune evasion. The ability of S. aureus to deploy different virulence factors must be taken into account for S. aureus vaccine design. Here we present a strategy for designing an effective vaccine against S. aureus disease by evaluating vaccine candidate performance in multiple in vivo models targeted to mimic aspects of human disease, and by co-development of functional in vitro immunoassays that measure the neutralization of relevant S. aureus virulence factors.